TEACHING ENGLISH IN MULTILINGUAL SOCIETIES - Irwan Prayitno (Universitas Negeri Padang, 2016)
In the era of globalization, Eglish becomes the most powerful and essential tool of communication. Consequently, teaching and learning English must be placed at a seriously important priority of educational system. In order to achieve the ideal outcome of teaching and learning English in multilingual society, three major aspects should be taken into account: 1) teachers, 2) teaching methods, and 3) teaching materials. The flourishing English teachers are always characterized by three dominant charateristics: 1) high degree of reflectivity, 2) high sense of efficacy, and 3) highly student-centered teching style. English teaching methods should be creatively developed in order to promote not only lower thinking order (memorizing and understanding) but also higher thinking order, especially creative thinking level. Finally, teaching English materials should be developed on the basis of students’ background knowledge and environment, the concepts, principles, values, and components for adapting didactic issues, and the higher thinking order.